2015
DOI: 10.3791/53262
|View full text |Cite
|
Sign up to set email alerts
|

Using <em>Ex Vivo</em> Upright Droplet Cultures of Whole Fetal Organs to Study Developmental Processes during Mouse Organogenesis

Abstract: Investigating organogenesis in utero is a technically challenging process in placental mammals due to inaccessibility of reagents to embryos that develop within the uterus. A newly developed ex vivo upright droplet culture method provides an attractive alternative to studies performed in utero. The ex vivo droplet culture provides the ability to examine and manipulate cellular interactions and diverse signaling pathways through use of various blocking and activating compounds; additionally, the effects of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The glucose concentration is crucial in the testis development process, especially for Sertoli cell differentiation from undifferentiated gonads [24]. A widely used DMEM (high glucose) supplemented with FBS or KSR was used for the culture medium in our experiments [9,29]. The success rates of the FBS-and KSR-supplemented groups were slightly different.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The glucose concentration is crucial in the testis development process, especially for Sertoli cell differentiation from undifferentiated gonads [24]. A widely used DMEM (high glucose) supplemented with FBS or KSR was used for the culture medium in our experiments [9,29]. The success rates of the FBS-and KSR-supplemented groups were slightly different.…”
Section: Resultsmentioning
confidence: 97%
“…These results suggested that, in our own culture system, the proper biological pressure was provided through the maintaining the gonadal morphology by the addition of a semi-cylindrical piece of gel. A culture method using a small volume of culture medium suitable for RNA interference and inhibitory chemical additional experiments has also been reported [22,29,34]. The results of the gonadal culture including the filter method may be improved if the morphology is maintained with a suitable holding material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another culture method is the hanging drop technique, in which testicular tissue fragments are cultured in a small volume of medium placed on the lid of a culture plate. This method has been used to explore the effects of chemical treatments on human and mouse testes and to study fetal vascularization, morphogenesis, and organogenesis[ 120 , 121 ]. Pendergraft et al [ 122 ] used a hanging drop approach to produce a functional testicular organ system by coculture with adult SSCs.…”
Section: Testicular Organoidsmentioning
confidence: 99%
“…An example of an organ-culture system is the hanging-drop method, where a fragment of testicular tissue is cultured within a small volume of medium placed on the lid of a culture dish. This method has been used to explore the effects of chemical treatments in human testis (Jorgensen et al, 2014) and to study human (Jorgensen et al, 2015) and murine (Potter and DeFalco, 2015) testicular development (Table II). Another organ-culture system is the air-liquid interface system, which consists of the culture of a small testicular tissue piece on a supportive stand and in simultaneous contact with the culture medium and the atmosphere.…”
Section: D Modelsmentioning
confidence: 99%